Cranial idiopathic hypertrophic pachymeningitis: A case report (2010)
Cranial idiopathic hypertrophic pachymeningitis is a rare disorder characterized by chronic inflammation causing thickening of the dura mater. Headache, multiple cranial neuropathy and magnetic resonance images showing GD-DTPA-enhanced thickened dura can aid diagnosis. We report the autopsy case of a 69-year-old man with chronic headache and visual loss due to optic nerve damage developing over a 3-month period, who was diagnosed with hypertrophic pachymeningitis. Cerebrospinal fluid showed inflammatory changes. The sample of hypertrophied dura mater revealed chronic granulomatous inflammation without signs of vasculitis or infectious or neoplastic processes. Idiopathic hypertrophic pachymeningitis is an exclusion diagnosis. Exhaustive tests (both bacteriological and histopathological) to identify the cause of dural thickening in our patient proved unsuccessful. © 2010 Academia de Ciencias Médicas de Bilbao.